Elective induction of labour and maternal request: a national population‐based study. (30th November 2015) - Coulm, B; Blondel, B; Alexander, S; Boulvain, M; Le Ray, C
Abstract : Objective: To estimate the rate of elective inductions in France and the proportion of them that were maternally requested, and to study the factors associated with elective inductions that were or were not requested by women. Design: Cross‐sectional population‐based study. Setting: All maternity units in France. Population: About 14 681 women from the 2010 French National Perinatal Survey of a representative sample of births. Methods: Inductions were classified as elective based on their indications and maternal and fetal characteristics, collected from medical records. Elective inductions requested by women were identified from the mother's postpartum interviews. Polytomous logistic regression analysis was used to study the determinants of inductions that were or were not maternally requested. Women with spontaneous labour served as the comparison group. Main outcome measure: Rate of elective inductions. Results: The induction rate was 22.6, 13.9% elective. Among elective inductions, 47.3% were requested by women. The characteristics of mothers, pregnancies, and maternity units were similar in both groups of elective inductions. The main associated factors were parity 2 or more [adjusted odds ratio (OR) 4.7, 95% confidence interval (CI) 3.1–7.2 for maternally requested inductions and aOR of 1.8 (95% CI1.2–2.7) for unrequested inductions, compared with parity 0] and private hospital status [aOR 4.5 95% (CI 3.3–6.0) for maternally requested inductions and aOR 3.7 (95% CI 2.8–4.9) for inductions not requested by the mother]. We found no association between maternal social characteristics and type of elective induction. Conclusion: Parity and organisational factors appear to influence the decision about elective inductions. It would be interesting to determine how obstetricians and women make this decision and for what reasons. Tweetable abstract: About 13.9% of inductions of labour were elective in France, 47.3% of these requested by women. Tweetable abstract: About 13.9% of inductions of labour were elective in France, 47.3% of these requested by women.